Vazão de uma motobomba acionada por painéis fotovoltaicos - Oyama, Paulo Takashi (2008)
This project evaluated the performance of a motor pump connected to two photovoltaic panels in order to determinate the outflow equations in relation to the solar irradiance on the photovoltaic panels. All data were collected between September 15th, 2007 and February 1st, 2008. For each lift height, it was verified: year, julian day, hour, panels temperature, motor pump voltage, panels voltage, solar irradiance at the panels plane, irradiance at the horizontal plane, motor pump outflow and pressure on the transducer. The outflow equations were obtained as a result of the solar irradiance on the photovoltaic panels plane for water lifts with heights between 2,2 and 18,2 meters, the equation varies according to the irradiance and the height of the lift and the efficiency equation of the water lift system in relation to the water height. The results pointed that for a water pumping system constituted by two photovoltaic modules and a motor pump used in this experiment, the outflow equation in relation to the solar irradiance and lift height, allows, with a margin of error of 17%, to calculate the water outflow, knowing the data of the average solar irradiance in the period and the needed height of the water lift, the efficiency of the water pumping system improved linearly according to the increase of the manometric height of the water lift.